Development of Student Worksheets (LKPD) Based on Scientific Literacy with Flare Context in Redox Reaction Material at SMAN 1 Tanjung Morawa - Raihan, Nina Kartika; Syuhada, Feri Andi (Universitas Lampung, 2024)
This research aims to determine the level of validity, teacher response and student response to student worksheets based on scientific literacy with flare contexts in redox reaction material. This development research uses a 4D development model which consists of 4 stages, namely, 1) Define, 2) Design, 3) Development, 4) Disseminate. Which is limited to the Development stage. The subjects in this research were 2 material expert validators, 2 media expert validators, 2 chemistry teachers, and class X Merdeka 10 students, totaling 33 students. Data collection instruments include interview, LKPD validation sheets, teacher questionnaire sheets, and student response questionnaire sheets. Based on the research results, the average assessment by material experts was 87.6% in the very appropriate category, the assessment by media experts was 93.9% in the very appropriate category, the average teacher response was 96.8% in the very appropriate category, and the results of the analysis of the response questionnaire Students have an average percentage of LKPD eligibility obtained, namely 81.4% in the